2022
DOI: 10.1038/s41467-022-29079-w
|View full text |Cite
|
Sign up to set email alerts
|

Atomic reconfiguration among tri-state transition at ferroelectric/antiferroelectric phase boundaries in Pb(Zr,Ti)O3

Abstract: Phase boundary provides a fertile ground for exploring emergent phenomena and understanding order parameters couplings in condensed-matter physics. In Pb(Zr1-xTix)O3, there are two types of composition-dependent phase boundary with both technological and scientific importance, i.e. morphotropic phase boundary (MPB) separating polar regimes into different symmetry and ferroelectric/antiferroelectric (FE/AFE) phase boundary dividing polar and antipolar dipole configurations. In contrast with extensive studies on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Recently, Fu et al reported an intermediate phase at the AFE/FE phase boundary of PZT, where antipolar and polar displacements of Pb-cations coexist. 46 This intermediate phase serves as a polar ordering “bridge” connecting the AFE and FE phases, similar to the monoclinic phases between the tetragonal and R phases at the morphotropic phase boundary (MPB). 47 Based on our observations, this intermediate phase exists when the applied E is smaller than E AF or E FA .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Fu et al reported an intermediate phase at the AFE/FE phase boundary of PZT, where antipolar and polar displacements of Pb-cations coexist. 46 This intermediate phase serves as a polar ordering “bridge” connecting the AFE and FE phases, similar to the monoclinic phases between the tetragonal and R phases at the morphotropic phase boundary (MPB). 47 Based on our observations, this intermediate phase exists when the applied E is smaller than E AF or E FA .…”
Section: Discussionmentioning
confidence: 99%
“…The main reflections {h00} and {hh0} in x = 0 sample display splitting and the superlattice diffraction peaks occurs around 1/2(110) p , supporting the average structure of the orthorhombic AFE state. 40 It is well-known that the origin of the 1/4(hkl) superlattice diffraction peaks is the antiparallel displacement of the A-site cation and the neighboring apex O 2− ions along the baxis, resulting in the antiferroelectric properties of PbZrO 3 and PLZT materials. 41,42 In the locally magnified diffraction peaks in the range of 36°∼ 45°, with the increasing BAN content, the specific peaks of (111) p are slightly split, and (200) p are gradually merged as well as the superlattice diffraction peaks around 1/2(110) p is weakened by degrees.…”
Section: ■ Experimentsmentioning
confidence: 99%
“…Considerable academic efforts have been made to improve the above parameters, such as structural heterogeneity, 8 designing textured ferroelectric ceramics, [9][10] constructing morphotropic phase boundary (MPB), [11][12] induced isolated-oxygen-vacancy, 13 etc. However, so far, element doping is still a simple and effective method that makes Pb(Zr,Ti)O 3 (PZT)-based ceramics more applicable to high-power applications.…”
Section: Introductionmentioning
confidence: 99%